Post-Notification Arrangements in Merging Business Entities (Mergers) as an Effort to Prevent Unfair Business Competition - Fahamsyah, Ermanto; Suri, Fadillah Atika (University of Jember, 2019)
One way a business actor strengthens their business is through cooperation with other business actors. One form of cooperation is a